Influence of Corporate Environmental Responsibility on Dimensions of Brand Equity in the Sustainable Food Industry - Escobar-Farfan, M (SAGE Publications Inc., 2024)
The objective of this study is to propose a theoretical model where corporate environmental responsibility (CER) influences brand loyalty (BL), perception of brand quality (PQ), brand awareness (BA), and the comparison brand (BC). A survey was carried out using an online questionnaire, and information was collected from 267. The research focuses on people who stated they were consumers of the sustainable food brand in Lima. To test the hypotheses of the proposed research model, the data were analyzed using the partial least squares path modeling method with SmartPLS software. The results showed a significant positive effect of CER on BL, PQ, BA, and BC. In conclusion, it can be stated that organizations that adopt sustainable practices and promote corporate environmental responsibility (CER) not only contribute to caring for the environment but can also improve essential aspects such as the equity of their corporate brand. Therefore, organizations must recognize the importance of taking transparent actions to strengthen the perception of their brand equity related to corporate environmental responsibility. This can translate into stronger customer loyalty and a more prominent position for sustainable food products. This study encourages prioritizing environmental responsibility, understanding that beyond contributing to the care of the environment, it also strengthens relevant aspects within the brand identity. © The Author(s) 2024.